2015
DOI: 10.1080/15548627.2015.1009797
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid-induced IgG production in TLR-activated human primary B cells involves ULK1-mediated autophagy

Abstract: (2015) Retinoic acid-induced IgG production in TLR-activated human primary B cells involves ULK1-mediated autophagy, Autophagy, 11:3, 460-471, DOI: 10.1080/15548627.2015 Keywords: antibody secretion, autophagy, B lymphocytes, CD180, plasma cell differentiation, retinoic acid, RP105, TLR9, ULK1Abbreviations: ATG, autophagy-related; BDS, bright detail similarity; CD180, CD180 molecule; CVID, common variable immune deficiency; ELISA, enzyme-linked immunosorbent assay; Ig, immunoglobulin; IL, interleukin; MAP1LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
(81 reference statements)
0
27
0
Order By: Relevance
“…27 out of the 131 genes tested significantly affected TLR signature gene expression, which included known TLR signaling components such as TICAM1, TBK1, MAPK9, RIPK3 and IRAK2 (Figure 3B). Furthermore, several phosphoproteins were reported to function in TLR signaling by independent studies: TRAFD1 (Sanada et al, 2008), STK3 (Geng et al, 2015), ULK1 (Eriksen et al, 2015), and CORO1A (Tanigawa et al, 2009). Interestingly, known and candidate components had similar effects on the TLR gene signature upon knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…27 out of the 131 genes tested significantly affected TLR signature gene expression, which included known TLR signaling components such as TICAM1, TBK1, MAPK9, RIPK3 and IRAK2 (Figure 3B). Furthermore, several phosphoproteins were reported to function in TLR signaling by independent studies: TRAFD1 (Sanada et al, 2008), STK3 (Geng et al, 2015), ULK1 (Eriksen et al, 2015), and CORO1A (Tanigawa et al, 2009). Interestingly, known and candidate components had similar effects on the TLR gene signature upon knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…MCL1 siRNA or control siRNA was introduced into purified normal B cells using the Nucleofector device (Amaxa Biosciences, Basel, Switzerland) in accordance with the manufacturer's instructions and the program U‐15, as previously described . Typically, 3 × 10 6 B cells were resuspended in 100 μl Nucleofector solution V and mixed with 0·06 n m siRNA.…”
Section: Methodsmentioning
confidence: 99%
“…RA exerts its effects primarily as a ligand for retinoic acid receptors (RARs) and retinoic X receptors (RXRs) acting as transcription regulators, and numerous genes have been identified as direct or indirect targets of RA‐mediated transcription . We have previously shown that RA stimulates normal human T cells, as well as normal B cells when activated via Toll‐like receptors (TLR) such as TLR9 and RP105 (CD180) . The natural ligand for TLR9 is bacterial and viral DNA rich in unmethylated CpG, and these ligands can be mimicked in vitro by synthetic unmethylated CpG oligonucleotides (CpG‐ODNs) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations